PENGARUH JUS JERUK TERHADAP TEKANAN DARAH PADA LANSIA YANG MENGALAMI HIPERTENSI DI WILAYAH KERJA PUSKESMAS TANGGULANGIN KABUPATEN SIDOARJO - Aminati, Fifi Ratna; Yastutik, Iryani Yuni; A'yun, Sofa Qurrata (LPPM STIKES HUSADA JOMBANG, 2024)
Hypertension or high blood pressure is a state of blood flow that consistently has high pressure on the arterial wall. The diagnosis of hypertension is made if the systolic blood pressure is above 140 mmHg and diastolic is above 90 mmHg on two measurements over a five-minute interval in a state of calm or rest. The purpose of this study was to analyze the effect of orange juice (citrus) on blood pressure in elderly people who have hypertension in the working area of the Tanggulangin Public Health Center. This type of research uses Pre-experiment with the design of one grub pre-posttest design. The population in this study were 33 elderly people in in the working area of the Tanggulangin Public Health Center. with a sample of a number of elderly people in in the working area of the Tanggulangin Public Health Center. totaling 30 people with sampling using the simple random sampling technique. The independent variable in this study was orange juice (citrus), blood pressure dependent variable. collection techniques used were observation and SOP. Processing using editing, coding, scoring and tabulating with the Wilcoxon test with α −25% (0.25) in p-value <α (0.25). The results showed that almost all respondents had high blood pressure of 30 people (100%), most of the respondents experienced a drop-in blood pressure after 21 people were given orange juice (70.0%). The results of the Wilcoxon test get a value of p = 0,000 < α = 0.05, because p < α, H1 is accepted and H0 is rejected. The conclusion of this study, there is the effect of orange juice (citrus) on blood pressure in the elderly in in the working area of the Tanggulangin Public Health Center.